여자대학생의 녹차 및 영양소 섭취와 피부건강상태의 관련성 - 정윤정(Yun-Jung Jung) (동아시아식생활학회지, 2021)
Several studies have investigated the relationship between diet and skin health. On the other hand, few studies have analyzed the effects of green tea intake on skin health. This study examined the effects of nutrient and green tea intake on the skin health condition by measuring skin hydration, elasticity, oil, pores, roughness, wrinkles, and melanin pigmentation in 104 female university students from Daegu, South Korea. The study subjects were divided into two groups: a green tea group who regularly drank two or more cups every day and a non-green tea group who did not drink any green tea. A questionnaire was used to obtain information from the study subjects regarding the amount and frequency of green tea intake and their nutrient intake. The skin health was analyzed using a skin diagnosis device. In summary, the average age of the subjects was 21.8 years old, and the mean BMI was 20.7 kg/m2, which was in the normal range. The mean intake of dietary fiber, vitamin C, and potassium were significantly higher in the green tea group than in the non-green tea group. The mean values for skin hydration, pores, elasticity, oil, roughness, and melanin pigmentation were also in the normal range. The skin condition parameters, such as skin hydration, pores, elasticity, roughness, and melanin pigmentation, were similar in both groups. On the other hand, the skin oil contents were significantly higher in the non-green tea group than in the green tea group. In general, a higher intake of antioxidant vitamins correlates with a lower degree of oil, pores, and roughness. In conclusion, green tea intake decreases the skin oil content in female university students. KCI Citation Count: 0